Organizational procedures more used in the classes of sport - Grettel Polo-Bugallo; Pablo Terry-Álvarez; Adolfo Polo-Jiménez (Universidad de Guantánamo, 2019)
In the planning of the sport class it plays an indispensable paper the organizational procedures. In the Sport Cocktail "Prince", county Havana deficiencies were detected in the methodological visits carried out to the classes: bad use of the organizational procedures, is not variety in the use of the same ones during the class. The objective is to carry out a wide study of the organizational procedures that you/they should be appealed to plan a class. The used methods are: the theoretical analyses and synthesis, historical - Logical, Inductive - Deductive and the empiric methods the observation and documental revision.